A review on role of artificial intelligence in food processing and manufacturing industry. (2022) - Ramirez-Asis, Edwin; Vilchez-Carcamo, Juan; Thakar, Chetan M.; Phasinam, Khongdet; Kassanuk, Thanwamas; Naved, Mohd
Abstract: Food is essential for humans. It is critical to decrease food waste, optimize the supply chain, and enhance food logistics, food delivery, and food safety. To a large extent, artificial intelligence and machine learning aid in accomplishing these goals. The increasingly widespread and sophisticated computing networks enable modern industrial and logistical systems. Data are continually created by sensors, machines, systems, intelligent devices and people inside these networks. This Big Data is analyzed quicker, more extensively and deeper than ever with increasing computer powers. These breakthroughs have redeveloped and created a new age known as Industry 4.0 or the Smart Factory, the value of artificial information technology (AI). This article discusses machine learning and artificial intelligence applications in the food industry and manufacturing. Major applications include supply chain optimization, crop selection, logistics, food delivery, and forecasting maintenance in food processing machines.